A real-time PCR technique in the identification of over-stunned slaughtered chicken - Amid, Azura; Ahmad Hassan, Nurhidayah; Abu Samah, Norshahida (2010)
Chickens were water stunned before slaughtered was acceptable in Malaysia under certain condition prepared by MAJLIS FATWA and JAKIM. However, in some country like Brunei this method was not accepted at all. Even in Malaysia, it is unlawful when these chickens were stunned over the current limit that set by JAKIM. The previous study conducted identified a candidate biomarker that suitable to be used in developing a detection method for over stunned chicken. A real-time PCR technique was applied as a detection method in this study using our identified biomarker in developing a set of specific primers. This study was conducted to observe the effectiveness of a detection method developed for identifying chicken that were stunning over the current limit allowable by JAKIM. Results of this study showed that by applying this detection method we were able to differentiate a chicken that was slaughtered according to original Syara’i method compared to the one that over stunned prior to slaughtering and also able to develop a result within 3 hours.